2015
DOI: 10.1111/dme.12754
|View full text |Cite
|
Sign up to set email alerts
|

Charcot foot syndrome

Abstract: Charcot foot syndrome is an uncommon complication of diabetes but is potentially devastating in its consequences. Outcome is made worse by widespread professional ignorance leading to delayed diagnosis, but it is also hampered by lack of understanding of its causes and lack of treatments with proven effectiveness, other than offloading. There remains a desperate need for studies into its causes as well as comparative audit and trials designed to determine the best treatment for this difficult condition. Such w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 86 publications
1
79
0
2
Order By: Relevance
“…Diagnosis is based on the history and clinical examination and timely imaging of the foot6. The pathogenesis of CN remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is based on the history and clinical examination and timely imaging of the foot6. The pathogenesis of CN remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While several biochemical mechanisms have been suggested to contribute to its development, the etiology of CN remains enigmatic . It is currently believed that CN occurs as a consequence of an imbalance of activity of two types of cells: osteoblasts and osteoclasts (Jeffcoate, 2015). This imbalance leads to enhanced bone lysis and fracture and is driven by inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Increased concentrations of TNF- and IL-6 were found also in sera of patients with CN (Petrova et al, 2015). CN has been associated with an increase in advanced glycation end products (AGEs) in blood that is often caused by poorly controlled diabetes and/or inflammation due to hyperglycemia and oxidative stress (Jeffcoate, 2015). It was found that AGEs stimulate apoptosis of human mesenchymal stem cells (Kume et al, 2005) and osteoblasts (Alikhani et al, 2007) by binding to receptor for AGE (RAGE) on their membranes (Witzke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Once a temperature difference of <2°C compared with the contralateral foot was achieved, he was provided with a custom-made ankle–foot orthosis with a modified shoe and was ambulatory after 15 months. DCN has an incidence of 0.1% per year in patients with diabetes mellitus and is not commonly seen in day-to-day practice by primary care physicians 1 2. It may not be considered among the differentials for unilateral erythematous foot swelling in a patient with diabetes mellitus and peripheral neuropathy and is often misdiagnosed as osteomyelitis, cellulitis, gouty arthritis or venous thrombosis.…”
mentioning
confidence: 99%
“…MRI is a sensitive modality for early acute Charcot's neuropathic osteoarthropathy and is helpful in distinguishing DCN from osteomyelitis 3. The treatment for DCN is different from that for common inflammatory conditions, and involves immobilisation in an irremovable TCC followed by use of modified shoes 1 2. A wrong or significantly delayed diagnosis may culminate in foot deformity, non-healing ulceration and limb amputation 4…”
mentioning
confidence: 99%